Organic electrochemical transistor array for recording transepithelial ion transport of human airway epithelial cells - Yao, Chunlei (Advanced materials (Deerfield Beach, Fla.), 2013)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.